Non-enzymatic glycosylation of myosin: effects of diabetes and ageing - Syrový, I; Hodný, Z (General physiology and biophysics, 1992)
The influence of diabetes mellitus, streptozotocin-induced diabetes and ageing on the non-enzymatic glycosylation of myosin from cardiac and skeletal muscles was investigated. In cardiac muscle, and to a lesser extent also in skeletal muscles of the rat, non-enzymatic glycosylation of myosin increases with the age, as measured in 6-, 12- and 29-month-old animals. Skeletal muscle myosin from diabetic humans and also that from diabetic rat cardiac muscle are more glycosylated when compared with control myosin preparations. Ca(2+)-ATPase activity of myosin is lower in muscles of diabetic individuals as compared with control muscles.
Keywords: Animals; svaly; Heart; experimentální diabetes mellitus; Ca2+-ATPasy; Calcium-Transporting ATPases; Myosins; Glycosylation; myosiny; Aging; srdce; diabetes mellitus; lidé; Humans; Aged; stárnutí; glykosylace; krysa rodu Rattus; vývoj svalů; Muscles; Diabetes Mellitus; senioři; zvířata; Myocardium; Muscle Development; myokard; Rats; Diabetes Mellitus, Experimental